"STARING INTO THE SINGULARITY" AND OTHER POSTHUMAN TALES: TRANSHUMANIST STORIES OF FUTURE CHANGE. Issue 2 (9th June 2021) - TAILLANDIER, APOLLINE
ABSTRACT: In this article, I conduct a contextual analysis of transhumanist conceptions of posthuman futures. Focusing on cryonics, nanotechnology, and artificial superintelligence technological projects through a study of primarily American sources from the 1960s onward, I identify three distinct conceptualizations of the posthuman future: Promethean, spontaneous, and scalar. I argue that transhumanists envision posthumanity as resulting from a transition that involves both continuity and radical change. Although these three posthuman futures appear to share an interest in predicting a superior "cosmic" realization of human destiny, they involve distinct "liberal" conceptions of historical agency. These include the unlimited individual liberty of the technologized self, the knowledge‐ordering properties of the market, and the rational aggregation of individual interests over the long term. I locate these heterogeneous and partly conflicting conceptions of historical agency in the context of the postwar crisis and remaking of liberalism's future. I argue that transhumanist ideas about the transition toward a more‐than‐human or beyond‐human future are best understood as manifesting a wide range of attempts at thinking about horizons of unprecedented change within the terms of postwar liberal projects. Ultimately, transhumanist futures shed light on the multiplicity of political temporalities that are required for thinking and writing stories about unprecedented futures.